2017
DOI: 10.3390/molecules22040636
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Bioactive Compounds in Broccoli as Affected by Cutting Styles and Storage Time

Abstract: Broccoli contains bioactive molecules and thus its consumption is related with the prevention of chronic and degenerative diseases. The application of wounding stress to horticultural crops is a common practice, since it is the basis for the fresh-cut produce industry. In this study, the effect of four different cutting styles (CSs) (florets (CS1), florets cut into two even pieces (CS2), florets cut into four even pieces (CS3), and florets processed into chops (CS4)) and storage time (0 and 24 h at 20 °C) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 46 publications
3
44
0
9
Order By: Relevance
“…We observed that glucoraphanin (GP) was the most abundant glucosinolate in the broccoli samples, as it has been previously reported for several broccoli varieties (Jones, Faragher, & Winkler, 2006;Torres-Contreras, Nair, Cisneros-Zevallos, & Jacobo-Velázquez, 2017). Both GP and sulforaphane content increased 24 h after processing.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed that glucoraphanin (GP) was the most abundant glucosinolate in the broccoli samples, as it has been previously reported for several broccoli varieties (Jones, Faragher, & Winkler, 2006;Torres-Contreras, Nair, Cisneros-Zevallos, & Jacobo-Velázquez, 2017). Both GP and sulforaphane content increased 24 h after processing.…”
Section: Discussionsupporting
confidence: 82%
“…The activation of the glucosinolates synthesis pathways is one of many plant responses to wounding (Mikkelsen, 2003). Different cutting styles have shown to induce variations in specific glucosinolates as well as their transformation into thiocyanates due to the releasing of myrosinase enzyme from specialized cells after cutting (Chen & Andreasson, 2001;Torres-Contreras et al, 2017). UV radiation (specifically the wavelengths in the UV-B spectrum) at low doses (0.45 kJ m -2 ) has also been demonstrated to elevate glucosinolates levels in broccoli sprouts which has been associated to the up-regulation of genes involved the biosynthetic pathway of aliphatic glucosinolates as well as of genes related to the response of pathogens and herbivores (Mewis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the caffeic acid in broccoli was present at trace level (Filannino et al ., ). Others have described that the content of caffeic acid was significantly increased after cutting, which could be related with increase in extractability due to the cell wall disruption (Torres‐Contreras et al ., ). The supernatant and juice fractions which have high phenolic compounds may potentially be used as functional beverages.…”
Section: Resultsmentioning
confidence: 97%
“…However, it also required extensive plasma clean-up during sample preparation, limiting the number of samples that could be handled at any given time. Given the relative fast thermal degradation of sulforaphane and its conjugates in human plasma at room temperature, with a reported half-life at 24 • C of between 6.16 and 0.49 h [27][28][29] and problems associated with sample degradation during lengthy plasma clean-up, a more rapid sample preparation methodology ahead of LC-MS would both allow processing of high numbers of samples, as would be required in large scale clinical trials, and may improve measurement accuracy. To that end, here we present a modified, cheaper, and high throughput method for the measurement of sulforaphane and its metabolites ( Figure 1) using LC-MS.…”
Section: Introductionmentioning
confidence: 99%